"Catching" Social Bias: Exposure to Biased Nonverbal Signals Creates Social Biases in Preschool Children. (February 2017) - Skinner, Allison L.; Meltzoff, Andrew N.; Olson, Kristina R.
Identifying the origins of social bias is critical to devising strategies to overcome prejudice. In two experiments, we tested the hypothesis that young children can catch novel social biases from brief exposure to biased nonverbal signals demonstrated by adults. Our results are consistent with this hypothesis. In Experiment 1, we found that children who were exposed to a brief video depicting nonverbal bias in favor of one individual over another subsequently explicitly preferred, and were more prone to behave prosocially toward, the target of positive nonverbal signals. Moreover, in Experiment 2, preschoolers generalized such bias to other individuals. The spread of bias observed in these experiments lays a critical foundation for understanding the way that social biases may develop and spread early in childhood.